2023
DOI: 10.3390/plants12030546
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnological Approach to Increase Oxyresveratrol Production in Mulberry In Vitro Plants under Elicitation

Abstract: Morus alba L. is used for a range of therapeutic purposes in Asian traditional medicine, and its extracts are reported to be effective against lipidemia, diabetes, and obesity, as well as being hepatoprotective and tyrosinase-inhibitory. They are also included in cosmetic products as anti-aging and skin-whitening agents. Stilbenes, the major bioactive compounds found in M. alba, have received renewed attention recently because of their putative activity against COVID-19. In this study M. alba plants were estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…So, several studies were published about the determination of this natural product in its sources or after use [194,195], as well as its isolation [196,197]. Moreover, biosynthesis and laboratory syntheses were widely published and reviewed [198], and many studies investigated the enhancement of oxyresveratrol bioproduction [199,200]. In other but related studies, the enhanced production of mulberry side A was reported [201].…”
Section: Figure 11mentioning
confidence: 99%
“…So, several studies were published about the determination of this natural product in its sources or after use [194,195], as well as its isolation [196,197]. Moreover, biosynthesis and laboratory syntheses were widely published and reviewed [198], and many studies investigated the enhancement of oxyresveratrol bioproduction [199,200]. In other but related studies, the enhanced production of mulberry side A was reported [201].…”
Section: Figure 11mentioning
confidence: 99%
“…Till now, this combined elicitation has not yet been accomplished using fully-suspended cell cultures of mulberry. Instead, it has only been performed using plantlets (Sabater-Jara et al, 2023) or in hydroxypropyl beta cyclodextrin-treated calli (Komaikul et al, 2019).…”
Section: Introductionmentioning
confidence: 99%